PREVALENCE OF IRON DEFICIENCY ANEMIA IN CHILDREN WITH CLEFT LIP AND CLEFT PALATE- A RETROSPECTIVE STUDY. - Varshini Chandrasekhar; Ashika Banu; Shami Kumar; Mohammed Syed (Student's Journal of Health Research, 2023)
Background: Cleft lip and/or cleft palate are the most prevalent craniofacial anomalies visible to the naked eye. Variations in haematological parameters can be used to determine if the immune system of these patients has been altered as a result of nutrition difficulties and recurrent infections. This study sought to determine the prevalence of malnutrition, including deficiencies in major micronutrients such as iron, folate, and vitamin B12, among children with cleft lip and/or palate, and to determine which nutritional interventions can improve the situation for these children. Methods:  All infants with cleft lip and/or cleft palate younger than 5 years who attended our institute were included. On their initial visit, the following were documented: demographic information, an assessment of malnutrition, and investigations including a complete blood count and peripheral blood film examination, as well as serum levels of albumin, ferritin, iron, folate, and vitamin B12. Results: The study included 115 patients, 26 (52%) of whom were male and 24 (48%) of whom were female. 19 (38%) had a cleft lip, 10 (20%) had only a cleft palate, and 21 (42%) had both clefts. Conclusion:  Iron deficiency is almost universally present in children with cleft lip and palate, according to a study. Therefore, iron and folic acid supplements should be administered upon initial contact to enhance iron reserve and haematological parameters for optimal and safe surgical outcomes.